Dynamics of SARS-CoV-2 Variants of Concern in Brazil, Early 2021 - Levi, José Eduardo; Oliveira, Cristina Mendes; Croce, Bianca Della; Telles, Paulo; Lopes, Annelise Correa Wengerkievicz; Romano, Camila Malta; Lira, Diego Bezerra; Resende, Anna Claudia Mello de; Lopes, Flávia Paiva; Ruiz, André Arroyo; Campana, Gustavo (Frontiers in Public Health, 2021)
Brazil is the country with the second-largest number of deaths due to the coronavirus disease-2019 (COVID-19). Two variants of concern (VOCs), Alpha (B.1.1.7) and Gamma (P.1), were first detected in December 2020. While Alpha expanded within an expected rate in January and February 2021, its prevalence among new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cases started to decrease in March, which coincided with the explosion of Gamma variant incidence all over the country, being responsible for more than 95% of the new cases over the following months. A significantly higher viral load [i.e., mean cycle threshold (Ct) values] for Gamma in comparison to non-VOC samples was verified by the analysis of a large data set of routine reverse transcription–PCR (RT–PCR) exams. Moreover, the rate of reinfections greatly increased from March 2021 onward, reinforcing the enhanced ability of Gamma to escape the immune response. It is difficult to predict the outcomes of competition between variants since local factors like frequency of introduction and vaccine coverage play a key role. Genomic surveillance is of uttermost importance for the mitigation of the pandemic.